Review of the Oriental genus Neoclarkinella Rema and Narendran, 1996 (Hymenoptera: Braconidae, Microgastrinae) with the description of two new species from India - Veena, T.; Ranjith, A. P.; Santhosh, S.; Kishore, Lambert (Zootaxa, 2014)
The rarely collected Oriental genus Neoclarkinella Rema and Narendran, 1996 is reviewed. Four species, all from India, are recognized of which two are described as new, namely Neoclarkinella janakikkadensis sp. nov., and N.narendrani sp. nov. from Kerala, India. A key to the oriental species of the genus is provided along with a character state matrix.